First Impression (Kesan Pertama) Masyarakat Desa Kakor Terhadap Gaya Berpakaian Mahasiswi Yang Fashionable (Studi Pada Masyarakat Desa Kakor, Kecamatan Ruteng, Kabupaten Manggarai) - Angelita Yeltri Egot; Lasarus Jehamat; Aelsthri Ndandara (Jurnal Pluralis, 2023)
The phenomenon of fashionable clothing is part of people's lives today, including female students in Kakor Village. The students appeared wearing hotpants, tight miniskirts above the knee, negligee/sleeveless dresses, and transparent clothing. This reaped a lot of impressions from the local community. The purpose of this research is to determine the impression of the people of Kakor Village on female students' clothing styles, and the factors that influence the public's impression of female students. The theory used in this research is social judgment theory. The impression itself cannot be separated from the observer's basic knowledge about something. As social assessment theory explains, when someone analyzes a message, they have a perception as a reference point, so the message will be seen from two sides, namely acceptance (assimilation effect) and rejection (contrast effect). This research uses a qualitative-descriptive approach, with data collection using observation, interviews and documentation techniques. The technique for determining informants is through purposive sampling. There were 12 informants in this study, with 9 key informants (community and community leaders) and 3 supporting informants (students). The results of the research show that the public's impression of female students' clothing styles is that they do not understand traditional values, are not good children, do not understand religious teachings, are disappointed, and show contemporary civilization. The impression conveyed is predominantly negative (rejecting). Several factors influence society's female students' clothing styles, namely the map of society's thoughts about women, culture and religion. The advice that the author recommends for society is that a perspective should not corner one party and judge someone not only by what they see. For female students, they should be critical in consuming popular products so that they are in harmony with up-to-date attitudes and the embodiment of local values.